PERFORMA REPRODUKSI IKAN NILEM (Osteochilus hasselti C.V.) BETINA TERPAPAR MEDIA MENGANDUNG K2Cr2O7 SEBAGAI ENDOCRINE DISRUPTOR AGENT - Purwo Raharjo; Windiriani Lestari; Gratiana Ekaningsih Wijayanti (Scripta Biologica, 2022)
Heavy metals can generally act as EDCs. Likewise chromium hexavalent may serve as a Endocrine Disrupter, especially the fish reproductive system. This study aims to determine the effect of chromium hexavalent on estradiol content, ovarian development and liver of nilem female (Osteochilus hasselti C.V.), the researchers also want to see the dose of chromium hexavalent most influential on estradiol levels, ovarian development, and liver of nilem fish (Osteochilus hasselti C.V.) as well as the interaction between reproduction parameters with water quality of maintenance media of nilem fish (Osteochilus hasselti C.V.).This study uses the method of "quantitative experimental". The experimental design was Completely Randomized Design with treatment of chromium hexavalent dose of 0, 0.009, 0.018, 0.027 and 0.036 mg/L performed in 5 replications at 3 stages, ie 1st, 2nd, and 3th months post-spawning maintenance. At 1st month of maintenance, chromium hexavalent did not significantly affect the reproductive parameters of GSI (Gonadosomatic Index), fecundity, HSI and estradiol. The chromium hexavalent had no significant effect on GSI, fecundity and estradiol and significantly affected HSI at 2nd months of maintenance. Chromium hexavalent significantly affected GSI, fecundity, HSI and estradiol in a 3th month maintenance trial.